Influence of Escherichia coli chaperone DnaK on protein immunogenicity. Issue 3 (7th December 2016) - Ratanji, Kirsty D.; Derrick, Jeremy P.; Kimber, Ian; Thorpe, Robin; Wadhwa, Meenu; Dearman, Rebecca J.
Summary: The production of anti‐drug antibodies can impact significantly upon the safety and efficacy of biotherapeutics. It is known that various factors, including aggregation and the presence of process‐related impurities, can modify and augment the immunogenic potential of proteins. The purpose of the investigations reported here was to characterize in mice the influence of aggregation and host cell protein impurities on the immunogenicity of a humanized single‐chain antibody variable fragment (scFv), and mouse albumin. Host cell protein impurities within an scFv preparation purified from Escherichia coli displayed adjuvant‐like activity for responses to the scFv in BALB/c strain mice. The 70 000 MW E. coli chaperone protein DnaK was identified as a key contaminant of scFv by mass spectrometric analysis. Preparations of scFv lacking detectable DnaK were spiked with recombinant E. coli DnaK to mimic the process‐related impurity. Mice were immunized with monomeric and aggregated preparations, with and without 0·1% DnaK by mass. Aggregation alone enhanced IgM and IgG2a antibody responses, but had no significant effect on total IgG or IgG1 responses. The addition of DnaK further enhanced IgG and IgG2a antibody responses, but only in the presence of aggregated protein. DnaK was shown to be associated with the aggregated scFv by Western blot analysis. Experiments with mouse albumin showed an overall increase in immunogenicity with protein aggregation alone, and the presence of DnaK increased the vigour of the IgG2a antibody response further. Collectively these data reveal that DnaK has the potential to modify and enhance immunogenicity when associated with aggregated protein. Abstract : Protein aggregation alone resulted in enhanced immunogenicity of a humanized single‐chain variable fragment (scFv) and mouse serum albumin in BALB/c mice. Addition of the recombinant Escherichia coli chaperone protein DnaK, at 0.1% by mass, to aggregated preparations further enhanced the IgG2a antibody response against both scFv and mouse albumin proteins. These data reveal that DnaK has the potential to modify and enhance immunogenicity when associated with aggregated protein.